Digital Engagement and Gender-Specific Drivers of Customer Satisfaction in the Insurance Mining Industry - Lassad Ben Dhiab,; Louail, Bilal; Riache, Siham (European Journal of Sustainable Development, 2025)
This study investigates the determinants of insurance customer satisfaction with a focus on the role of digital engagement and their gender-specific effects. Since digital platforms now increasingly shape the field of determining customers' expectations, this study uses advanced statistical models like logistic regression, random forests, and gradient boosting to analyze the association between digital engagement, lowly paid premiums, and customer satisfaction. Findings indicate that web participation is a powerful predictor of satisfaction, where more participation correlates with increased satisfaction, particularly for male customers. Gender-based results indicate that female customers are highly sensitive to affordability for premiums, and thus the price strategy should be developed for this group. The study also identifies nonlinear interactions and interaction effects among such important variables as income, education, and the degree of engagement for which a customer is committed. This suggests the worth of tailored plans for customer engagement. The study contributes to the literature by introducing an advanced framework for the analysis of customer behavior among insurers, demonstrating the power of advanced analytics in uncovering underlying patterns and relationships. Therefore, insurers are required to invest in digital channels that provide differentiated experiences, gender-sensitive pricing, and segmenting customers into categories to provide more accurate solutions. Future studies are also called for in the research to examine the degree to which trust and privacy concerns underlie digital engagement, as well as examine other demographic variables that influence customer satisfaction. Keywords: Digital Engagement, Customer Satisfaction, Insurance Industry, Gender-Specific Impacts.